NEUROTIC BECHAVIOR AS A CONTEMPORARY SOCIAL PHENOMENON - Dunaeva, Victoria (PEOPLE: International Journal of Social Sciences, 2019)
Contemporary world requires excellent psychological adaptation. It is very important for people to recognize the power within themselves and understand lessons they are learning. If they listen carefully themselves, it would be easier for them to live without fears, hesitations, obsessions and other kinds of neurotic behavior. However, survival efforts of many individuals turn out to be futile and they are not capable to adjust to values of modern society. They feel unable to keep the rhythm of changing life and cope with the challenge of its time: globalization. Dynamics of their lives and their negative emotions related to it become out of their control. In this chapter I would like to present my observations as a clinical psychologist. I am going to explore the following issues: what does mean today to be neurotic? What are the signs of neurotic personality? How do psychologists explain the reasons for neurotic behaviour of contemporary people? Why humans cannot be adapted to modern life?